Earlier treatment initiation is associated with a decreased number of HIV-1 subtype A1 transmissions in Greece. Issue 3 (19th June 2020) - Kostaki, Evangelia Georgia; Hodges-Mameletzis, Ioannis; Magiorkinis, Gkikas; Adamis, Georgios; Xylomenos, Georgios; Nikolopoulos, Georgios; Lazanas, Marios; Chini, Maria; Mangafas, Nikos; Skoutelis, Athanasios; Papastamopoulos, Vasileios; Antoniadou, Anastasia; et al.
Abstract : Objectives: Subtypes A1 and B are the most prevalent HIV-1 clades in Greece. Subtype A1 epidemic is highly monophyletic and corresponds to transmissions that occurred locally. Our aim in this molecular epidemiology analysis was to investigate the role of early treatment in preventing new HIV-1 transmissions. Methods: Our analysis focused on 791 subtype A1 sequences from treatment-naïve individuals in Greece. Estimation of infection dates was performed by molecular clock calculations using Bayesian methods. We estimated the time interval between (1) the infection and sampling dates (linkage to care window), (2) the sampling dates and antiretroviral therapy (ART) initiation (treatment window), and (3) the infection dates and ART initiation (transmissibility window) for the study population. We also inferred the putative source of HIV infections between individuals of different groups divided according to the length of treatment, linkage to care or transmissibility window. Results: A significant decline was detected for the treatment window during 2014–2015 versus the 2 previous years (p=0.0273), while the linkage to care interval remained unchanged during the study period. Inference of the putative source of HIV infections suggested that individuals with a recent diagnosis or narrow transmissibility window (time period between HIV infection and ART initiation) were not sources of HIV infections to other groups. Contrarily, a significant number of HIV infections originated from individuals with longer transmissibility window interval. Conclusions: Our findings showed that the treatment window is decreasing over time, presumably due to the updated treatment guidelines. Our study also demonstrates that people treated earlier after infection do not transmit at high rates, thus documenting the benefits of early ART initiation in preventing ongoing HIV-1 transmission.